Pelatihan Dasar Manajemen dan Legalitas Usaha untuk Peningkatan Pendapatan Usaha Mikro Kecil Menengah - Nur Laili Fikriah; Mega Noerman Ningtyas; Fikriyatul Azizah Su’ud (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
BAZNAS Microfinance Sawojajar is an institution that has several MSME partners. However, the MSMEs face several major problems, namely a lack of understanding of basic management such as marketing, finance, operations, and human resources as well as minimal business legality, such as a Business Identification Number (NIB) and halal certification. These problems hinder business development and reduce their competitiveness. This community service activity aims to provide concrete solutions through basic training in business management and legality using the Asset-Based Community Development (ABCD) approach. This training involved 30 MSMEs which was carried out comprehensively, covering theory and practice related to marketing, financial recording, SOP preparation, human resource management, to making business legality. The results of the activity showed an increase in participants' understanding of business management and business legality, which is expected to have an impact on business sustainability and increased income. This program also encourages MSMEs to be more independent in developing their businesses sustainably.